Student and Instructor Perspectives on the English Preparatory School’s ELT Program: A Needs Analysis Study - Gülşah Coşkun Yaşar; Pinar Mercan Küçükakın; S. Aslıhan İleri (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study was to identify the needs of the students and the teachers regarding the ELT curriculum implemented in the school of foreign languages at a public university and to provide recommendations for curricular improvements. The study utilized a qualitative research method, and the case study model was applied. Semi structured interviews were conducted with 8 SFL instructors and two focus group interviews were conducted with 12 students enrolled in the program. As part of this NA study, all SFL teachers were invited to participate in workshop discussions. Eight groups were formed, each assigned a discussion topic. Topics and prompts were based on preliminary findings from teacher and student interviews. To support the interview and workshop data, researchers analysed key documents on curricular issues. Weekly meeting minutes from level coordinators and results from the SWOT analysis conducted at the SFL were also retrieved. The researchers analysed and interpreted the gathered data using content analysis. Findings revealed several needs areas regarding syllabi, assessment and evaluation, instructional materials, and implementation. This study offers important implications for instructors, administrators, and policymakers to make more effective curricular decisions and improve the quality of education at the SFL and similar language teaching settings.